2020
DOI: 10.1515/jpm-2020-0308
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a prediction model on vaginal birth after caesarean in a The Netherlands: a prospective cohort study

Abstract: ObjectivesDiscussing the individual probability of a successful vaginal birth after caesarean (VBAC) can support decision making. The aim of this study is to externally validate a prediction model for the probability of a VBAC in a Dutch population.MethodsIn this prospective cohort study in 12 Dutch hospitals, 586 women intending VBAC were included. Inclusion criteria were singleton pregnancies with a cephalic foetal presentation, delivery after 37 weeks and one previous caesarean section (CS) and preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…As an example of the use of the ARIMA modeling, a study evaluated the performance of some states on infant mortality and showed that the method was satisfactory in its predictions, showing that some states would not be able to reach the 2017 national policy target of 29 deaths per 1,000 live births by 2019 ( 48 ) . In this way, forecasting methods can be applied to transform care practices and direct the development of public health policies ( 52 ) , in addition to being a methodology that allows the use of data from official sources and low operational costs ( 53 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the use of the ARIMA modeling, a study evaluated the performance of some states on infant mortality and showed that the method was satisfactory in its predictions, showing that some states would not be able to reach the 2017 national policy target of 29 deaths per 1,000 live births by 2019 ( 48 ) . In this way, forecasting methods can be applied to transform care practices and direct the development of public health policies ( 52 ) , in addition to being a methodology that allows the use of data from official sources and low operational costs ( 53 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of this type of modeling in the decision-making and health policy-making process in poorer countries is still a challenge, whether due to the absence or fragility of the systematic collection of epidemiological data, or the difficulty of consolidating quality information systems and establishing a culture of data usage ( 53 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Como ejemplo del uso del modelado ARIMA, un estudio evaluó el desempeño de algunos estados sobre la mortalidad infantil y mostró que el método fue satisfactorio (48) . Así, los métodos de pronóstico pueden ser aplicados para transformar las prácticas asistenciales y direccionar la elaboración de políticas públicas de salud (52) , además de ser una metodología que permite utilizar datos de fuentes oficiales y de bajo costo operacional (53) .…”
Section: Aspectos éTicosunclassified
“…El uso de este tipo de modelaje en el proceso decisorio y formulador de políticas en salud en los países más pobres aún es un desafío, ya sea por la ausencia o fragilidad en la recogida sistemática de datos epidemiológicos, o por la dificultad de consolidar sistemas de información de calidad e instaurar una cultura de utilización de datos (53) .…”
Section: Aspectos éTicosunclassified
“…The authors further created a graphic normogram and an easy-touse online calculator that can predict individual chances for successful TOLAC. Following its publication, studies tried to validate the MFMU's calculator in different populations and settings [9][10][11][12][13][14] with conflicting results.…”
Section: Introductionmentioning
confidence: 99%